Screening Nature: The Landscape in the Age of Instagram - Lamberti, Paola (Aisthesis, 2025)
This paper explores the complex and dynamic relationship between digital media, screens and nature, proposing a reinterpretation of landscape in the age of Instagram: this should not be appreciated both as an immutable natural entity and as a touristic commodity object, but as an aesthetic assemblage reshaped and renegotiated through digital practices and experiences. Starting from the Schellingian conception of nature as a work of art in the making, landscape is not a static reality, but an aesthetic form in continuous transformation and entangled with phenomenologies and technologies, with bodies, technical cultures and scopic regimes, with cultural positionings and pragmatic attitudes. In contrast to ecocriticism and with an unilateral negative and nondialectical perspective, sometimes all too pronounced and explicit, which denounces the reduction of landscape to mere anthropocentric, socio-economic and cultural, aesthetization, the paper – through a specific analysis of three instagram profiles – aims to show how social media foster the rediscovery of nature – both as intact beauty or as terrific wasted land – through participatory and interactive narratives. The role of digital media in the aesthetic renegotiation of landscape is explored, emphasising the mix of image, text and social interaction. Finally, future perspectives are scketched, because digital visual culture can transform and re-activate the landscape as a dynamic archive of memories, identities and ecological awareness.